The first born of all creatures (Col 1.15) in the Commentary to John of Origen (Pontificia Universidad Católica de Chile. Facultad de Teología, 2011)
Before briefly analyzing each use of this expression, the author provides a general context for understanding the thought of Origen in this Commentary, with respect to what most interests the author regarding this subject. Thus, Logos is outlined as God in general; then the author goes on to refine the relationship with creatures, the Father and the Spirit, and ends with an introduction to the epsilon pi ivol alpha l, above all, wisdom. This context is accompanied, in the notes, by several bibliographical citations and by some other relevant texts from other works of Origen. Then the author presents 23 uses of the pericope, refering to the mediation between the Father and creation, emphasizing the divine in the mediator, the Son, Logos, and the archetypal image. Applied to the embodied, the divine in Christ is expressed. This corresponds to the moderate or hierarchical subordinationism of Origen. This is confirmed by analyzing its use in Origen's other works, some of which are noted by the writer.